Emerging Technologies Transforming Therapy - Weaver, Edward; Lamprou, Dimitrios (Journal of Medical Science, 2023)
The advancement of healthcare therapies is under constant development due to changing demographics and evolving disease-states. To ensure continuous furtherance of the healthcare system capacity to treat such ailments, emerging technologies (ETs) are coming to the forefront of medicine. It’s the hope that ETs are capable of covering a broad scope of therapeutic treatment areas, enabling novel pharmaceutical pathways to be established. Highlighted in this mini review are examples of focus ET areas, including additive manufacturing (AM), microfluidics (MFs), microelectromechanical systems (MEMS) and machine learning (ML), that have shown promising qualities and should be targeted further to improve patient outcomes.